Categorial Model of Four-Line Diagrammatic Representations Recognition - Yu A Chudina; N A Chudina (RUDN Journal of Psychology and Pedagogics, 2012)
The geometrical model of recognizing four-line diagrammatic representations, characterized by different relations of elements, has been constructed in the article. The averaged superthreshold estimations of the perceptive differences between the four-line configurations have been processed by means of the multidimensional scaling technique. The constructed space has been interpreted in terms of Sokolov and Izmailov's spherical model of differentiating stimuli. The characteristics of the derived model reflect the representation recognition mechanism based on categorical attributes.